A National Study of Teaching and Assessing Writing in Canadian Middle Grades Classrooms - Peterson, Shelley; McClay, Jill (McGill Journal of Education / Revue des sciences de l'éducation de McGill, 2014)
This article reports comprehensive findings from a national study of the teaching and assessment of writing in classrooms across ten Canadian provinces and two of three territories. Through interviews with 216 grade 4-8 teachers and observations and interviews in 22 classrooms (1 to 3 classrooms in each province), we gathered information about participating middle-grade teachers’ goals, and the practices and resources (including computers and multi-media, parents and community resources) that they use to teach and assess writing. The strengths and challenges that they identify in teaching writing and assessing writing, and the people who have most greatly influenced their writing instruction provide additional information on which we base implications for teacher education and professional development initiatives.